Wildfire-water supply risk in montane watersheds of Colorado: baseline assessment and evaluation of mitigation strategies - Gannon, Benjamin Michael, author; Wei, Yu, advisor; Cheng, Antony, advisor; Kampf, Stephanie, committee member; Thompson, Matthew, committee member (Colorado State University. Libraries, 2020)
This is a multi-part dissertation examining wildfire-water supply risks and the mitigation effectiveness of land and fire management solutions. Chapters 2, 3, and 4 were prepared independently for publication elsewhere. Chapters 1 and 6 provide brief bookends to discuss the motivations for this research and conclusions drawn from the three independent but related research chapters. Chapter 5 discusses common limitations of the risk models used in the research chapters and opportunities for improvement. (CHAPTER 2) In fire-prone watersheds, concern over wildfire impacts to water supplies has motivated efforts to mitigate risk by reducing forest fuels. Methods to assess fuel treatment effects and prioritize their placement are needed to inform risk mitigation. We introduce a fuel treatment optimization model to minimize risk to multiple water supplies based on constraints for treatment feasibility and cost. We quantify risk as the expected sediment impact costs to water supplies by combining measures of fire likelihood and behavior, erosion, sediment transport, and water supply vulnerability. We demonstrate the prioritization framework on two watersheds in the Colorado Front Range. Our results suggest wildfire risk to water supplies can be meaningfully reduced by treating dense, fire-prone forests on steep slopes near water supplies. However, we found that the cost of fuel treatment outweighs the expected cost savings from reduced sediment by a considerable margin due to the high cost of thinning forests and the low expected fuel treatment-wildfire encounter rate. This highlights the importance of expanding the use of more cost-effective treatments, like prescribed fire, and identifying fuel treatment projects that benefit multiple resources. (CHAPTER 3) Water supply impairment from increased contaminant mobilization and transport after wildfire is a major concern for communities that rely on surface water from fire prone watersheds. We introduce a Monte Carlo simulation method to quantify the likelihood of wildfire impairing water supplies beyond limits for treatment by combining stochastic representations of annual wildfire and rainfall activity. Water quality impairment is evaluated in terms of turbidity limits for treatment by modeling wildfire burn severity, post-fire erosion, sediment transport, and suspended sediment dilution in receiving waterbodies. Water supply disruption is analyzed at the system level based on the impairment status of water supply components and their contributions to system performance. We use this approach to assess wildfire-water supply impairment and disruption risks for a system of water supply reservoirs and diversions in the Front Range Mountains of Colorado, USA. Our results show that wildfire may impair water quality in a concerning 15.7-19.4% of years for diversions from large watersheds. Reservoir impairment should be extremely rare for large, off network reservoirs (at most 0.01% of years) but occur in as many as 2.8% of years for smaller, on network reservoirs. System redundancy meaningfully reduced disruption risk for alternative conveyance routes (4.3-25.0% reduction) and almost eliminated disruption risk for a pair of substitutable terminal sources (99.9% reduction), whereas dependency among conveyance reservoirs nearly doubles risk of conveyance disruption. Our results highlight the importance of considering water system characteristics when evaluating wildfire-water supply risks. (CHAPTER 4) In many fire-prone watersheds, wildfire threatens surface water drinking supplies with post-fire contaminant mobilization and transport. We evaluated the potential to mitigate this risk by limiting fire sizes and watershed effects with a containment network of manager-developed Potential fire Operational Delineations (PODs) using wildfire risk transmission methods to partition the effects of many stochastically simulated wildfires to within and out of POD burning. We assessed water supply impacts with two metrics – total sediment load and water quality impairment above suspended sediment concentrations for treatment – using a linked fire-erosion-sediment transport model. Our results suggest that improved fire containment could substantially reduce wildfire risk by 13.0 to 55.3% depending on impact measure and post-fire rainfall. Containment based on the manager-developed PODs had greater potential in our study system to reduce total sediment load than it did to avoid water quality impairment because fires within many of the larger PODs resulted in impairment even when contained. Much of the residual impairment risk after containment originated from less than 20% of the PODs, suggesting strategic investments to further compartmentalize these areas of the landscape could improve the effectiveness of the containment network. Similarly, risk transmission occurred most frequently across control features in certain parts of the network, indicating that efforts to increase containment probability with fuels reduction would have a disproportionate effect if prioritized in these areas.
Keywords: fire containment; systems analysis; wildfire risk; fuels reduction; erosion; water supplies